Development of a Control Strategy for the Hybrid Energy Storage Systems in Standalone Microgrid - Guentri, Hocine; Dahbi, Abdeldjalil; Allaoui, Tayeb; Aoulmit, Salim; Bouraiou, Ahmed (International Journal of Electrical and Computer Engineering Systems, 2023)
The intermediate energy storage system is very necessary for the standalone multi-source renewable energy system to increase stability, reliability of supply, and power quality. Among the most practical energy storage solutions is combining supercapacitors and chemical batteries. However, the major problem in this kind of application is the design of the power management, as well as the control scheme of hybrid energy storage systems. The focal purpose of this paper is to develop a novel approach to control DC bus voltage based on the reference power's frequency decomposition. This paper uses a storage system combined of batteries and supercapacitors. These later are integrated in the multi-source renewable energy system to supply an AC load. This technique uses the low-pass filters' properties to control the DC bus voltage by balancing the generated green power and the fluctuating load. The hybrid storage system regulates power fluctuations by absorbing surplus power and providing required power. The results show good performances of the proposed control scheme, such as low battery current charge/discharge rates, lower current stress level on batteries, voltage control improvements, which lead to increase the battery life.